Setting up a Jason Agent on Top of ROS to Control an Autonomous UAV - Calegari, Felipe da C.; Silvestre, Iago O.; Hübner, Jomi F.; Becker, Leandro B.; Brito, Maiquel de (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC); 2025: Anais do XIX Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações, 2025)
This paper describes the nuances related to properly setting up a Jason agent on top of the Robot Operating System (ROS) to control an autonomous Unmanned Aerial Vehicle (UAV) executing in a Gazebo simulation. To do so we refactor a previously developed search-and-rescue (SAR) UAV application with updated technology. We mainly address changing the interaction mechanism between the agent and ROS, i.e., the way that the agent interacts with its “physical body”. We also address using Docker technology to setup the design environment and speed up the design process. Our results showed that it can be challenging to adapt agents since different technologies have different setups and different compatibilities, but it comes with advantages such as scalability in agent programming and constant updates to work with different ROS versions.